18F-FDG PET/CT scan standardised uptake value (SUV) score for diagnosis, staging and monitoring malignancy in spinal melanotic schwannoma. Issue 12 (7th December 2022) - Haleem, Shahnawaz; Mahmoud, Mohamed H; Singh Kainth, Gurvinder; Botchu, Rajesh; Hassan, Md Faizul
Abstract: Melanotic schwannoma (MS) is a rare nerve sheath neuroectodermal neoplasm. We highlight the use of F18-fluorodeoxyglucose positive emission tomography/computed tomography (18F-FDG PET/CT) standardised uptake value (SUV) results in the diagnosis, staging and monitoring of spinal MS. A 58-year-old female patient had a 6-month history of left leg pain (S1) and no skin lesions. Magnetic resonance imaging reported a possible schwannoma with CT-guided biopsy, indicating a metastatic malignant melanoma. 18F-FDG PET/CT scan revealed only sacral destruction and an SUV score of 3.6. Histopathology results confirmed a malignant melanotic peripheral nerve sheath tumour (schwannoma). In MS, the 18F-FDG PET/CT scan SUV cut-off point can be used to distinguish between benign and malignant lesions, whereas (SUVmax ) can predict the histologic response and therefore useful as a 'screening test'. Our case highlights the increased uptake on PET/CT by melanocytic variant of neurogenic tumours and clinicians need to be aware of this.